Exposure to tobacco smoke increases bone loss in spontaneously hypertensive rats. (12th May 2018) - Xu, Jingyi; Qiu, Xing; Liang, Zhou; Smiley-Jewell, Suzette; Lu, Faqiang; Yu, Mang; Pinkerton, Kent E.; Zhao, Dewei; Shi, Bingyin
Abstract: Purpose: To define if exposure to tobacco smoke (TS) could induce reduction of bone mass and impairment of bone architecture, features observed in osteoporosis in normotensive rats and the influence of TS exposure on the osteoporotic features exhibited in the spontaneously hypertensive (SH) rats. Methods: Normotensive Wistar Kyoto (WKY) and SH rats were exposed to filtered air or TS for 8 weeks, then their proximal femurs were extracted for micro-computed tomography (micro-CT) assessment, histological and immune-histological examinations to quantify the adverse influence of TS exposure on the bone mass and density, as well as bone architecture. Results: We found that TS exposure not only induced significant decreases in bone mineral density (BMD), bone volume (BV), cortical and trabecular thickness (Ct.Th and Tb.Th), trabecular surface area (Tb.Ar), expression of hypoxia-inducible factor-1α (HIF-1α) in the trabecular marrow, delayed ossification of cartilage, as well as statistical increases in trabecular separation (Tb.SP) and the number of trabecular marrow adipocytes in both WKY and SH rats, but also exacerbated multiple features of osteoporosis exhibited in SH rats, including decreased BMD, Ct.Th, Tb.Ar, HIF-1α expression, delayed cartilage ossification, and increased Tb.SP. Conclusions: Our results show that TS exposure can reduce bone mass and impair bone architecture and exacerbate multiple features of osteoporosis exhibited in SH rats.